Management of a Pregnancy Complicated by Pompe Disease - Jennifer Weida; B. E. Hainline; C. Bodkin; M. K. Williams (Case Reports in Obstetrics and Gynecology)
Background. As more women with metabolic muscle diseases reach reproductive age, knowledge of these diseases and their impact on pregnancy is necessary. Case. 23-year-old G1P0 with juvenile-onset Pompe disease (PD) delivered a viable infant by cesarean section at 32 weeks and 6 days. The pregnancy was complicated by worsening maternal pulmonary status, muscular strength, and mobility. Conclusion. The management of pregnancies complicated by Pompe disease requires a multidisciplinary approach, including expertise in neuromuscular disease, maternal-fetal medicine, biochemical genetics, pulmonology, anesthesia, and dietetics.